Global church planting : biblical principles and best practices for multiplication - Ott, Craig, 1952-; Wilson, Gene, 1953- (Grand Rapids, Mich. : : Baker Academic, ., 2011)
Combining substantive biblical principles and missiological understanding with practical insights, this book walks readers through the various models and development phases of church planting. It emphasizes the role of the missionary church planter, advocating methods that lead to church multiplication.--From publisher description.
The task of church planting -- The reasons for church planting -- New Testament beginnings -- Church multiplication and indigenous church-planting movements -- Apostolic church planters -- The shape of the church -- Pioneer, reproduction, and regional approaches to church planting -- The developmental phases of a church plant : an overview -- Preparing, part 1 : targeting and commissioning -- Preparing, part 2 : understanding and strategizing -- Launching : evangelism and discipleship -- Establishing : congregating and maturing -- Structuring : expanding and empowering -- Reproducing : strengthening and sending -- The personal life of church planters -- Church-planting teams -- Developing servants, leaders, and planters -- Partnerships and resources in church planting -- Planting churches with kingdom impact.
Includes bibliographical references (p. 419-441) and index.
Keywords: Church development, New